Is the blue wall of silence a fallacy in cases of police sexual misconduct? - Sweeting, Fay (International journal of police science & management, 2022)
Police sexual misconduct encompasses a range of behaviours: from sexually inappropriate language directed towards colleagues or members of the public to engaging in sexual relationships with vulnerable members of the public. All types of police misconduct are thought to be under-reported, in part because of the ‘blue wall of silence’ where police officers fail to report colleagues’ wrongdoing for reasons of loyalty and a fear of retribution. A sample of 382 English police officers were invited to assess eight fictional police sexual misconduct scenarios to ascertain whether the scenario was a breach of the Code of Ethics, the expected level of discipline and if they would report the officer. Reporting likelihood was increased when officers perceived the scenario to be a breach of the Code of Ethics and worthy of a higher level of discipline. Female officers were more likely to report sexual misconduct than male officers, and scenarios involving direct colleagues were less likely to be reported. Non-reporting was greatest for sexual harassment between colleagues and the seriousness of this behaviour was minimised as justification for non-reporting. Use of confidential reporting was minimal with direct reporting to a line manager to be the preferred option.